Clinical Features and Outcomes in Patients Presenting with Plasmodium Falciparum - Khan, Noor Ullah; Kakar, Kaleemullah; Gulandam; Gulzar, Mohammed Atif; Ahmed Babar, Shahzada Dawood; Afzal, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Despite international efforts to lessen its effects, Plasmodium falciparum malaria continues to pose a serious threat to public health in endemic areas. There is little information available on the clinical characteristics and results of P. falciparum infections, in contrast to P. vivax, which is more commonly in South Asia. The purpose of this study was to assess the range of P. falciparum-related clinical symptoms and sequelae among hospitalized patients in a Pakistani tertiary care facility. Objective: To determine the common clinical features, complications, and outcomes in adult patients presenting with Plasmodium falciparum malaria. Methods: Over the course of six months, Bolan Medical College/Hospital conducted this qualitative, descriptive cross-sectional study. Using sequential sampling, 167 patients with proven P. falciparum infections between the ages of 18 and 65 were included. Physical tests and structured interviews were used to document clinical characteristics and problems. Co-morbid conditions such as cancer, autoimmune diseases, chronic liver disease, or recent blood transfusions were not included in the study. Results: Fever was universal (100%), followed by chills and rigors (92.2%), headache (71.9%), vomiting (64.7%), and myalgia (58.7%).Common physical signs included pallor (68.9%), hepatomegaly (47.3%), splenomegaly (37.7%), jaundice (36.5%), and altered consciousness (17.3%) Major complications observed were malarial hepatitis (37.7%), acute kidney injury (24.5%), severe anemia (19.2%), cerebral malaria (8.4%), ARDS (5.3%), and multi-organ dysfunction (4.4%). Conclusion: Plasmodium falciparum malaria in this study presented with a broad clinical spectrum and substantial risk for serious complications. Malarial hepatitis and AKI were the most common complications, while cerebral malaria and ARDS, though less frequent, signaled severe disease. Early recognition of atypical presentations and prompt, comprehensive management are essential to reducing morbidity and mortality in endemic regions.